2018
DOI: 10.1021/acs.cgd.8b00581
|View full text |Cite
|
Sign up to set email alerts
|

Pressure–Temperature Phase Diagrams and Transition Mechanisms of Hybrid Organic–Inorganic NH···N Bonded Ferroelectrics

Abstract: The ferroelectric–paraelectric transitions of 1,4-diazabicyclo[2.2.2]­octane (dabco) tetrafluoroborate (dabcoHBF4) and perchlorate (dabcoHClO4), between their phases II (orthorhombic space group Pm21 n) and I (tetragonal space group P4/nmm) proceed at T C = 377 and 378 K, respectively. On approaching phase I the anions are strongly shifted by about 0.8 Å and become disordered, but the protons remain ordered in the NH+···N bonds. In phase I, the disordered protons and anions approximate the tetragonal space gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
14
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 37 publications
(83 reference statements)
2
14
2
Order By: Relevance
“…Despite the wrong space group and lattice parameters, the structural model presented by Li et al . in their figure 1 (D and F) is consistent with the correct larger unit cell and symmetry determined in our single-crystal experiments ( 5 ). The symmetry relation between the ferroelectric and paraelectric phases is of primary importance.…”
supporting
confidence: 88%
See 3 more Smart Citations
“…Despite the wrong space group and lattice parameters, the structural model presented by Li et al . in their figure 1 (D and F) is consistent with the correct larger unit cell and symmetry determined in our single-crystal experiments ( 5 ). The symmetry relation between the ferroelectric and paraelectric phases is of primary importance.…”
supporting
confidence: 88%
“…They incorrectly describe the symmetry of paraelectric phases of dabcoHClO 4 and dabcoHBF 4 as space group P 4/ mmm (No. 123) with the unit cell containing one ionic pair ( Z = 1), while, as shown in our previous study ( 5 ), the true space group is P 4/ nmm (No. 129) and the unit cell is two times larger ( Z = 2).…”
mentioning
confidence: 53%
See 2 more Smart Citations
“…Szafrański and Katrusiak stated that the space group of the paraelectric structure of [Hdabco]ClO 4 and [Hdabco]BF 4 is P 4/ mmm ( 1 4 ). In 2018, they overturned their previous results and suggested that the space group is P 4/ nmm ( 5 ) according to neutron-diffraction measurements. While the subtle nature of P 4/ mmm and P 4/ nmm structures could be appreciated from the marked drop of the intensity of the reflections with the sum of Bragg indices h + k odd, Szafrański and Katrusiak misused the reflection (034) in their neutron diffraction measurements [figure 4 of ( 5 )], which unfortunately did not obey the Bragg indices h + k odd ( 6 ).…”
mentioning
confidence: 67%